POLITENESS OF VERBAL AND NON-VERBAL DIRECTIVE SPEECH ACTS IN THE TENTH GRADE STUDENTS’ LEARNING PROCESS OF NEGERI 1 MATARAM - Lindayana Lindayana; Arifuddin Arifuddin; Halus Mandala (RETORIKA: Jurnal Ilmu Bahasa, 2018)
This research aims at knowing: (1) the realization of politeness of verbal and non-verbal directive speech acts of students, (2) deviations on politeness principles of students’ directive speech acts, and (3) the determining factors to the politeness and non-politeness of verbal and non-verbal directive speech acts for the Tenth Grade students of SMA Negeri 1 Mataram in the process of learning in the classroom. Research subjects in this study were the teachers who taught Indonesian, English, Economics, History, Mathematics, Religion, Civics, and Natural Sciences (IPA), and all students who are in class X of IPS 2, IPA 1 and IPA 3 in SMA Negeri 1 Mataram. This research belongs to qualitative descriptive study. The data were collected using observation method. The results of this study showed that: (1) there is the emergence of speech acts of the verbal and non-verbal directive of the students in the learning process, such as directive speech acts of rebuking, commanding, banning, advising, asking, reminding, satirizing, suggesting, threatening, rebuking, and (2) there is deviation of the principle of politeness of directive speech acts that is deviation of principle of one maxim, two maxim, and deviation of three maxim, and (3) there are influencing factors for the politeness and non-politeness of verbal and non-verbal directive speech acts of students in the learning process , including linguistic and non-linguistic factors.